Testing the feasibility of the startle-first route to deimatism - Grace G. Holmes (Nature Portfolio, 2018)
Abstract Many prey species perform deimatic displays that are thought to scare or startle would-be predators, or elicit other reflexive responses that lead to attacks being delayed or abandoned. The form of these displays differs among species, but often includes prey revealing previously-hidden conspicuous visual components. The evolutionary route(s) to deimatism are poorly understood, but it has recently been suggested that the behavioural component of the displays evolves first followed by a conspicuous visual component. This is known as the “startle-first hypothesis”. Here we use an experimental system in which naïve domestic chicks forage for artificial deimatic prey to test the two key predictions of this hypothesis: (1) that movement can deter predators in the absence of conspicuously coloured display components; and, (2) that the combination of movement and conspicuously coloured display components is more effective than movement alone. We show that both these predictions hold, but only when the movement is fast. We thus provide evidence for the feasibility of ‘the startle-first hypothesis’ of the evolution of deimatism.